2008
DOI: 10.1177/0310057x0803600613
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Wedge versus Pelvic Wedge in Preventing Hypotension following Combined Spinal Epidural Anaesthesia for Caesarean Delivery

Abstract: Aortocaval compression is a major cause of maternal hypotension. A randomised controlled clinical trial was designed to compare two wedged supine positions for prevention of hypotension following combined spinal epidural anaesthesia for caesarean delivery. Sixty parturients undergoing elective caesarean delivery were randomly assigned to two different wedged supine positions. After the completion of subarachnoid injection, parturients were placed with either a wedge under the right pelvis (group P, pelvic wedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Zhou et al found higher SBP during the first min in patients using a lumbar wedge versus a pelvic wedge. 22 The clinical relevance of this finding and its relationship to nausea and vomiting are unknown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhou et al found higher SBP during the first min in patients using a lumbar wedge versus a pelvic wedge. 22 The clinical relevance of this finding and its relationship to nausea and vomiting are unknown.…”
Section: Discussionmentioning
confidence: 97%
“…14-17 The second compares lateral or tilted supine positions with the complete supine position, [18][19][20][21] and the third compares different locations of wedges or right-tilted vs. left-tilted positions. 22,23 The current study could be classified in the last of these three groups because it compared the use of a lumbar-pelvic wedge with the complete supine position. The results show that hypotension occurred frequently and that the wedge used was ineffective in reducing the incidence of maternal hypotension, but that patients with the wedge required less vasopressor and experienced fewer episodes of nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study was designed to examine CO changes only in three preoperative positions and one postoperative position before and after neuraxial anaesthesia, respectively; in normal clinical obstetric anaesthesia practice, a range of different positions, such as left lateral, right lateral, head up, sitting, head down and pelvic tilt, are employed during establishment and maintenance of neuraxial anaesthesia. [39][40][41][42][43] Large longitudinal studies incorporating pre-pregnancy, pregnancy and post-partum TTE measurements until at least six months post partum should be designed to evaluate serial changes in CO during pregnancy. Further studies should also specifically examine the effects of posture and anaesthesia in subgroups of women based on initial preoperative CO as well as the effect of posture on CO in the presence of neuraxial and general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 48 articles with our search strategy of which 37 [945] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that acute surveillance, i.e. actively asking study subjects whether undesired events occurred by use of structured questionnaires, interviews or diagnostic tests at predefined time intervals, is more effective than passive disclosure [44, 45]. Reporting of adverse events should already be considered during study design since data on adverse events are less susceptible to bias and confounders when they are collected prospectively rather than retrospectively [54, 55].…”
Section: Discussionmentioning
confidence: 99%